The “Replication Crisis” and Trust in Psychological Science: How Reforms Shape Public Trust in Psychology - Nicole Methner; Barbara Dahme; Claudia Menzel (Social Psychological Bulletin, 2023)
Failed replications can jeopardize public trust in psychological science and recent findings cast doubt on the idea that self-corrections and reforms can rebuild this trust. These findings are in contrast to trust repair research that proposes changes in transparency, norms, and policies as trust repair mechanisms. This raises the question of whether the used experimental material is one reason behind these unexpected findings. Previous studies used short texts that may give too little information on the replication crisis and initiated reforms in the field. In a pre-registered experiment (N = 390), we, therefore, tested whether comprehensive information about the replication crisis and reforms increases public trust in psychology, compared to a control condition that only informs about the replication crisis. To give comprehensive information, we created an animated video for each experimental condition. After watching the video, participants indicated their trust in researchers, trust in past research findings, and trust in current research findings. As expected and in line with trust repair research, information about reforms increased trust in researchers and in current (vs. past) research, compared with information about the replication crisis and its causes only. We discuss the generalizability of our results and implications for communicating the replication crisis to the public.